Cervical Cancer in Ethiopia: Survival of 1, 059 Patients Who Received Oncologic Therapy. (20th June 2014) - Kantelhardt, Eva Johanna; Moelle, Ulrike; Begoihn, Matthias; Addissie, Adamu; Trocchi, Pietro; Yonas, Bekuretsion; Hezkiel, Petros; Stang, Andreas; Thomssen, Christoph; Vordermark, Dirk; Gemechu, Tufa; Gebrehiwot, Yirgu; et al.
Abstract: Background: Almost 500, 000 women are newly diagnosed with cervical cancer (CC) every year, the majority from developing countries. There is little information on the survival of these patients. Our primary objective was to evaluate consecutive CC patients presenting over 4 years at the only radiotherapy center in Ethiopia. Methods: All patients with CC from September 2008 to September 2012 who received radiotherapy and/or surgery were included (without brachytherapy). Vital status was obtained through telephone contact or patient cards. Results: Of 2, 300 CC patients, 1, 059 patients with standardized treatment were included. At the end of the study, 249 patients had died; surviving patients had a median follow-up of 16.5 months; the 10% and 90% percentiles were 3.0 and 32.7 months, respectively. Mean age was 49 years (21–91 years). The majority of patients presented with International Federation of Gynecology and Obstetrics stage IIb–IIIa (46.7%). Because of progression during the waiting time (median 3.8 months), this proportion declined to 19.3% at the beginning of radiotherapy. The 1- and 2-year overall survival probabilities were 90.4% and 73.6%. If assuming a worst-case scenario (i.e., if all patients not available for follow-up after 6 months had died), the 2-year survival probability would be 45.4%. Conclusion: This study gives a thorough 4-year overview of treated patients with CC in Ethiopia. Given the limited treatment availability, a relatively high proportion of patients survived 2 years. More prevention and early detection at all levels of the health care system are needed. Increasing the capacity for external-beam radiation as well as options for brachytherapy would facilitate treatment with curative intention. Abstract : The primary objective was to evaluate outcome of consecutive cervical cancer patients treated over 4 years at the only radiotherapy center in Ethiopia. Two-year overall survival was 73.6%. Promoting early detection and increasing … Increasing the capacity for external-beam radiation as well as options for brachytherapy would facilitate treatment with curative intention.